Hidden Salem - Hooper, Kay (Hooper, Kay. Bishop/Special Crimes Unit novel, 2020)
"A town shrouded in the occult. An evil that lurks in the dark. The SCU returns in a hair-raising novel from New York Times bestselling author Kay Hooper. Nellie Cavendish has very good reasons to seek out her roots, and not only because she has no memory of her mother and hardly knew the father who left her upbringing to paid caregivers. In the eight years since her twenty-first birthday, very odd things have begun to happen. Crows gather near her wherever she goes, electronics short out when she touches them, and when she's upset, really upset, it storms. At first, she chalked up the unusual happenings to coincidence, but that explanation doesn't begin to cover the vivid nightmares that torment her. She can no longer pretend to ignore them. She has to find out the truth. And the only starting point she has is a mysterious letter from her father delivered ten years after his death, insisting she go to a town called Salem and risk her life to stop some unnamed evil. Before her thirtieth birthday. As a longtime member of the FBI's Special Crimes Unit, Grayson Sheridan has learned not to be surprised by the unusual and the macabre--but Salem is different. Evidence of Satanic activities and the disappearance of three strangers to the town are what brought Salem to the attention of the SCU, and when Gray arrives to find his undercover partner vanished, he knows that whatever's hiding in the seemingly peaceful town is deadly. But what actually hides in the shadows and secrets of Salem is unlike anything the agents have ever encountered."--Provided by publisher.